Histopathological changes and evaluation of resistance in Asian rice (Oryza sativa L.) against rice root-knot nematode, Meloidogyne graminicola Golden & Birch. - Mhatre, Priyank Hanuman; Pankaj, Pankaj; Malik, S.K.; Kaur, Sukhdeep; Singh, Ashok Kumar; Mohan, Sharad; Sirohi, Anil (The Indian Journal of Genetics and Plant Breeding, 2016)
The rice root-knot nematode, Meloidogyne graminicola is one of the major pest of the rice-wheat cropping system, and is responsible for considerable yield reductions. Resistance against M. graminicola in rice could be most valuable in alleviating this problem. In the present study, 64 rice cvs./landraces were evaluated for resistance against rice root-knot nematode on the basis of root-knot index. Our study showed a large variation in susceptibility and sensitivity to M. graminicola infection among the rice cvs./ landraces examined. Out of the total 64 rice cvs., seven (Abhishek, Khaja, Super Sugandhamati, Kishori Dehraduni, Gaudeshwari, Tuniaslet, Chima Kamin) had less than 10 galls/plant and of these, Abhishek exhibited a strong resistance response with least number of galls (2 galls/ plant) and necrotic browning of roots. The nematode females in the roots of cv. Abhishek were smaller in size compared to those on the highly susceptible cv. Bangla Patni.The histopathological studies showed that the giant cells collapsed and degenerated before the J2s developed into adults. The resistant trait exhibiting rice cultivar, Abhishek, holds promise for resistance breeding and also for identifying resistance gene/s against M. graminicola.